Foliar Potassium and Boron Can Improve Mandarin Yield and Quality - Tripti Vashisth (EDIS, 2022)
This article summarizes findings of a two year fertilizer study evaluating effect of foliar applied potassium, calcium, and boron on quality of Mandarin. The fertilizers evaluated in this study were on top of standard soil-applied fertilizer program. For two consecutive years foliar potassium and boron combination was found to improve yield and quality of ‘Tango’ mandarin.